2015
DOI: 10.1208/s12249-015-0284-2
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Effective and Safe Gene Carriers by Grafting Alkyl Chains to Generation 5 Polypropyleneimine

Abstract: Abstract. Gene therapy is a novel method to treat a variety of diseases including genetic disorders and cancer. Nonviral gene carriers have now gained considerable attention as gene carrier systems. Polyamidoamine (PAMAM) and polypropyleneimine (PPI) are the two most widely used denderimers in gene delivery studies. The aim of the current study was to investigate the effects of modification of generation 5 polypropyleneimine (G5 PPI) dendrimers with alkanoate groups as hydrophobic moieties on DNA transfection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The ethidium bromide exclusion assay proved the ability of modified carriers to condense DNA, while the transfection assay showed higher DNA delivery efficiency compared to that of pristine G5 PPI and Superfect TM (Qiangen, Milan, Italy). 3-(4,5-Dimethylthiazol-2-yl)-2,5-di phenyltetrazolium bromide (MTT) and apoptosis experiments showed lower toxicity for modified carriers compared to unmodified PPIs [138]. Additionally, arginine-conjugated PPIs were prepared as non-toxic and efficient gene delivery carriers [139].…”
Section: Poly(propyleneimines) (Ppi)mentioning
confidence: 99%
See 1 more Smart Citation
“…The ethidium bromide exclusion assay proved the ability of modified carriers to condense DNA, while the transfection assay showed higher DNA delivery efficiency compared to that of pristine G5 PPI and Superfect TM (Qiangen, Milan, Italy). 3-(4,5-Dimethylthiazol-2-yl)-2,5-di phenyltetrazolium bromide (MTT) and apoptosis experiments showed lower toxicity for modified carriers compared to unmodified PPIs [138]. Additionally, arginine-conjugated PPIs were prepared as non-toxic and efficient gene delivery carriers [139].…”
Section: Poly(propyleneimines) (Ppi)mentioning
confidence: 99%
“…Important structural modifications have been made to improve the TE and reduce PPIs' toxicity. Hashemi et al reported the modification of a G5 PPI with C6, C10, and C16 alkanoate groups inserted as hydrophobic moieties [138]. The ethidium bromide exclusion assay proved the ability of modified carriers to condense DNA, while the transfection assay showed higher DNA delivery efficiency compared to that of pristine G5 PPI and Superfect TM (Qiangen, Milan, Italy).…”
Section: Poly(propyleneimines) (Ppi)mentioning
confidence: 99%
“…A small library of alkanoate-modified PPI G5 dendrimers was developed and tested for their ability to transfect DNA to neuroblastoma Neuro-2a cells. It was shown that a balanced hydrophobic surface modification results in improved transfection, low cytotoxicity, and hemotoxicity [124]. Much larger modifications of PPI dendrimers in order to increase their efficiency as gene carriers have been made by a team of researchers from The State University of New Jersey [123][124][125][126].…”
Section: Clinical Studies Of Dendrimers For Targeted Cancer Therapymentioning
confidence: 99%
“…Apoptotic cells were determined by staining using the propidium iodide (PI) method described elsewhere (Hashemi et al 2015). In brief, MCF-7 cells were seeded at a density of 2 Â 10 4 cells per well in 48-well plates.…”
Section: Pi Stainingmentioning
confidence: 99%